National education and the state : an historical geography of the emergence of national education in pre-Famine Ireland - Lougheed, Kevin (Trinity College (Dublin, Ireland). Department of Geography, 2014)
This thesis examines the geography of the national education system in pre-Famine Ireland. Foucault's theory of governmentality and Jessop's strategic-relational approach have been utilised to situate this study in a broader theoretical context. In doing so, it has been possible to examine the spatial interactions between region specific networks of social relations and the rationale of the state that attempted to increase its control in Ireland. The interplay between the governmental rationale and wider social networks varied over space and resulted in the emergence of distinct regions of national school establishment.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin